LPCAT1 overexpression promotes the progression of hepatocellular carcinoma - He, Rong-Quan; Li, Jian-Di; Du, Xiu-Fang; Dang, Yi-Wu; Yang, Lin-Jie; Huang, Zhi-Guang; Liu, Li-Min; Liao, Liu-Feng; Yang, Hong; Chen, Gang (Cancer Cell International, 2021)
Hepatocellular carcinoma (HCC) remains one of the most common malignant neoplasms. Lysophosphatidylcholine acyltransferase 1 (LPCAT1) plays a key role in the lipid remodelling and is correlated with various neoplasms. Nonetheless, the biological functions and molecular mechanisms of LPCAT1 underlying HCC remain obscure.